2022
DOI: 10.12911/22998993/145457
|View full text |Cite
|
Sign up to set email alerts
|

An Experimental Investigation into Improving the Performance of Thermoelectric Generators

Abstract: Low-temperature heat sources have become increasingly popular in recent years, particularly for energy generation. The majority of thermal devices in the market (including devices using solar energy, geothermal energy, waste energy, and so on) transform heat into electricity indirectly, requiring mechanical work before producing power. Through the Seebeck effect, the technology that employs a thermoelectric generator (TEG) may directly transform heat energy into electricity. The TEG technology provides several… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 16 publications
0
13
0
Order By: Relevance
“…Several experimental and theoretical studies [13][14][15][16] examined heat transfer from the TEG surface in order to improve its performance and its power generation. TEG with heat pipe heat sink has been investigated with variable fin space, fin length, fin height, fin materials for both natural and forced convection to enhance the TEG performance [17,18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several experimental and theoretical studies [13][14][15][16] examined heat transfer from the TEG surface in order to improve its performance and its power generation. TEG with heat pipe heat sink has been investigated with variable fin space, fin length, fin height, fin materials for both natural and forced convection to enhance the TEG performance [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…To have a high-power generation from TEG the heat transfer from the cold surface should be increased. This could be done by fins or forced convection as performed in [13,26] and many other researches. Such methods require fans and extra volume for fins which may not be available in many applications specially the medical or built-in application.…”
Section: Introductionmentioning
confidence: 99%
“…If AWH machine is to be competitive, then the produced water price must be reduced by reducing energy consumed per litre, energy cost, maximising water harvested or if water is to be transported long distances, where its cost may rise to 0.7 $/L [7,8]. In order to maximise the harvested water amount, thus reducing SEC, research on enhancing heat transfer including fin natural/forced convection [9,10] or different technique must be used.…”
Section: Introductionmentioning
confidence: 99%
“…In (Alahmer et al, 2022) have been experimentally tested and compared with liquid evaporation mode with different heat fluxes using free and forced convection, so the results revealed that when compared to free convection without fins, adopting forced steam convection would improve the TEG voltage fluctuations 435.9%.…”
Section: Introductionmentioning
confidence: 99%